Axonal Kainate Receptors Modulate the Strength of Efferent Connectivity by Regulating Presynaptic Differentiation - Sakha, Prasanna; Vesikansa, Aino; Orav, Ester; Heikkinen, Joonas; Kukko-Lukjanov, Tiina-Kaisa; Shintyapina, Alexandra; Franssila, Sami; Jokinen, Ville; Huttunen, Henri J.; Lauri, Sari E. (Frontiers in Cellular Neuroscience, 2016)
Kainate type of glutamate receptors (KARs) are highly expressed during early brain development and may influence refinement of the circuitry via modulating synaptic transmission and plasticity. KARs are also localized to axons, however, their exact roles in regulating presynaptic processes remain controversial. Here, we have used a microfluidic chamber system allowing specific manipulation of KARs in presynaptic neurons to study their functions in synaptic development and function in vitro. Silencing expression of endogenous KARs resulted in lower density of synaptophysin immunopositive puncta in microfluidically isolated axons. Various recombinant KAR subunits and pharmacological compounds were used to dissect the mechanisms behind this effect. The calcium permeable (Q) variants of the low-affinity (GluK1-3) subunits robustly increased synaptophysin puncta in axons in a manner that was dependent on receptor activity and PKA and PKC dependent signaling. Further, an associated increase in the mean active zone length was observed in electron micrographs. Selective presynaptic expression of these subunits resulted in higher success rate of evoked EPSCs consistent with higher probability of glutamate release. In contrast, the calcium-impermeable (R) variant of GluK1 or the high-affinity subunits (GluK4,5) had no effect on synaptic density or transmission efficacy. These data suggest that calcium permeable axonal KARs promote efferent connectivity by increasing the density of functional presynaptic release sites.